Small and Medium Enterprises (SMEs) Financing in Bangladesh: A Review of Literature - Islam, K. M. Anwarul; Karim Miajee, Md. Rezaul (International Journal of Small and Medium Enterprises, 2018)
The paper has talked about writing accord among approach creators, financial specialists, and business specialists that small and medium enterprise (SMEs) are drivers of monetary development. A sound SME segment contributes unmistakably to the economy through making greater work openings, creating higher generation volumes, expanding sends out and presenting advancement and enterprise skills.The dynamic job of SMEs in creating nations safeguards them as motors through which the development targets of creating nations can be accomplished.